Using mathematical modeling in training planning - Busso, T.; Thomas, L. (International Journal of Sports Physiology and Performance, 2006)
This report aims to discuss the strengths and weaknesses of the application of systems modeling to analyze the effects of training on performance. The simplifications inherent to the modeling approach are outlined to question the relevance of the models to predict athletes' responses to training. These simplifications include the selection of the variables assigned to the system's input and output, the specification of model structure, the collection of data to estimate the model parameters, and the use of identified models and parameters to predict responses. Despite the gain in insight to understand the effects of an intensification or reduction of training, the existing models would not be accurate enough to make predictions for a particular athlete in order to monitor his or her training.